PYHIN protein IFI207 regulates cytokine transcription and IRF7 and contributes to the establishment of K. pneumoniae infection - Mills, Kingston; Bowie, Andrew; Mc Loughlin, Rachel (My University, 2023)
PYHIN proteins AIM2 and IFI204 sense pathogen DNA, while other PYHINs have been shown to regulate host gene expression through as-yet unclear mechanisms. We characterize mouse PYHIN IFI207, which we find is not involved in DNA sensing but rather is required for cytokine promoter induction in macrophages. IFI207 co-localizes with both active RNA polymerase II (RNA Pol II) and IRF7 in the nucleus and enhances IRF7-dependent gene promoter induction. Generation of Ifi207−/− mice shows no role for IFI207 in autoimmunity. Rather, IFI207 is required for the establishment of a Klebsiella pneumoniae lung infection and for Klebsiella macrophage phagocytosis. These insights into IFI207 function illustrate that PYHINs can have distinct roles in innate immunity independent of DNA sensing and highlight the need to better characterize the whole mouse locus, one gene at a time.
PUBLISHED
cited By 0
Keywords: Klebsiella macrophage phagocytosis; IFI204 sense pathogen DNA; Transcriptional regulation; Klebsiella pneumoniae; Innate immunity; Cytokines; PYHIN proteins; RNA polymerase II; TNF; IRF7; CP: Immunology